Competencies of Engineering Graduates: What are the Employer’s Expectations? - Najwa Azmi, Aini; Kamin, Yusri; Khair Noordin, Muhammad (International Journal of Engineering and Technology, 2018)
Recently, universities keep receiving complaints from the industries regarding the capability of engineering graduates when starting their new job. The complaints were always about the inability of the engineering graduates to adapt in the industry. This is due to minimum exposure of industrial training period given by university to them. As a result, most of fresh engineering graduates do not have enough industry experience that is demanded by industry. Worse case, there is mismatching skill during industrial training which not relevance to what they are studied before. This problem contributes to unemployment issue among engineering fresh graduates. The purpose of this paper is to review and analyse about the engineering competencies from all over the world. The paper is written on extensive secondary data analysis. It is revealed that the criteria needed by employers from most developed countries are almost similar. Based on summary, technical and non-technical skills are both important to become a competent engineer. There are some recommendations to develop and improve both technical and non-technical skills that can be emphasized by authorities of higher education especially in Malaysia.Â Â